Exploring Young Consumers' Satisfaction with Online and Offline Banking Services: : The Motivation of Switching Between Banks in the UK - Ofori, Felix Nana Kofi; Gibson, Ammar; Appiah, Kenneth (Archives of Business Research, 2022)
Purpose: The main objective of this article examines the differences in the switching behaviours of older (Generation X and baby boomers) and younger (Millennials and Generation Z) customers of banks in the UK, with emphasis is on online and offline banking services. The secondary objective is also to evaluate the influential factors of customer satisfaction in the banking sector relating to customer switching behaviours. Design and Methodology: The study adopts a positivist approach by using questionnaire survey to gather data from 106 clients of banks in the UK. The questionnaire comprises 30 questions, the majority of which use a 5-point Likert scale. Findings: No statistically significant difference is found when the switching behaviours of older and younger customers are compared. However, younger customers perceived online banking as more useful due to their greater ease-of-use. Critically, security and ease-of-use are the most noticeable determinants of customer satisfaction influencing switching behaviours. Research Limitations: This study lacks a managerial perspective on switching behaviours. This means that the applicability of the findings to banks in the UK is limited, suggesting that a further exploration in that respect may be warranted. Practical Implications: Banks in the UK are urged to re-focus their customer relationship strategies to improve security and perceived ease-of-use. It is also recommended that marketing campaigns are launched to inform the clients about the benefits of online banking with a specific emphasis on perceived usefulness and ease-of-use.